(untitled) - David Harris (Orlando, Florida, 1995)
The book provides computer information systems (CIS) students with a microcomputer-based "systems" book emphasizing practical problem-solving tools and strategies. It combines traditional systems development life cycle (SDLC) techniques with modern fourth-generation language (4GL) and computer-assited systems engineering (CASE) technology to teach students how to build small-enterprise computer information systems
Keywords: management information,systems analysis,systems design